(untitled) (Journal of Philosophy Culture and Political Science, 2025)
Under conditions of increasing political transformation and change in the realities of Kazakhstan, the human rights discourse becomes increasingly important as a site for the articulation of alternative value systems and critical reflection of public order. This study aims to identify levels of value consciousness in the public rhetoric of four leading Kazakh human rights defenders based on the theory of spiral dynamics. The study analyzes the texts of four human rights defenders with a legal education, actively participating in public space between 2016 and 2024. The methodology of work is based on a combined content-analysis, paragraph coding and construction of a categorical matrix vMEMEs, adapted to the human rights and legal discourse. The reliability of the coding was tested using the Cohen’s Kappa method (κ=0.82), which indicates a high degree of consistency in the evaluations. The results of the analysis show the dominance of three levels of value consciousness, namely blue, where it is about normative, legal and order. Next is the green, which implies inclusion, solidarity and humanism, and the yellow, which includes systemic thinking, reflexivity, and adaptability. For each of the speakers, individual variations in the configuration of levels and rhetorical strategies are fixed. Elements of red, violet and, in some cases, turquoise levels were also identified, which indicates the existence of transitional forms of consciousness and strategic adaptation. The scientific novelty of the research is the first empirical application of the theory of spiral dynamics to the analysis of human rights rhetoric in the Kazakh context. The theoretical significance lies in the development of a cognitive-value approach to the study of civil consciousness. The practical applicability of the results consists in the possibility to use the proposed methodology for monitoring value transformations, predicting the evolution of civic rhetoric, as well as for educational and primary education purposes. Keywords: spiral dynamics, human rights discourse, vMEMEs, social conflicts, Kazakhstan, civic consciousness.